Evaluación de los Beneficios del Centro de Interpretación Ambiental para el Bosque de Protección Alto Mayo - Sector Venceremos - San Martin 2011" - Tuesta Gonzales, Carla Carol (2012)
The Environmental Center Interpretation has become a useful and important tool for tbe care and education of visitors and inhabitaots of the Venceremos sector knowing tbe importance of tbe cooservation and study of the natural resources in your area. The evaluation of tbe Environmental Center- Interpretation (CIA). it allows to know tbe basic infrastructure, the services that drink, thc economic, social and environmental benefits that the center of interpretation is generating in tbe sector which must be strengthened to ensure its sustainability with economic ahernatives in harmony with the forest, to achieve this should be weU defined tbe responsibilities of the different actors and especially ensuring tbe participation of society .now we will defeat the sector increased its economic activity since the implementation oftbe CIA. Also the population of the V enceremos Sector, is organized more, appreciates and knows tbe dynamics ofthe Alto Mayo Protection Forest (BP AM), reflected in tbe reduction of 4% of tbe extraction of natural resources generating a positive dynarnism with tendency to continue to grow, the proposal shall be considered important to sustainability as: the implementation of an area for the marketing of handicrafts, charging for admission to the CIA, as a way to promote the realization of complementary economic activities that would help to mitigate the negative impact of local populations on the BP AM, which will ensure its permanence in time. Key words: natural resources, environmental benefits